Hands-on Competencies and Social-Based Skills of Practicum Trainees: Basis for Students’ Skills Enhancement - Francisco, Adrian (Technium Social Sciences Journal, 2026)
Preparing students for employment so they can contribute to society has been one of the paramount goals of higher education institutions. In fact, in the levelling of state colleges and universities (SUCs) in the Philippines, productivity has always been measured by the statistics of graduates who are gainfully employed (CHED-DBM Joint Circular NO. 1, 2016). This study attempts to ascertain whether there is a relationship between the social-based skills and hands-on competency skills of the practicum trainees of the University of Antique. The descriptive-correlational method was employed in the study. A total of 106 practicum trainees were purposively selected and served as the study’s subjects, who were evaluated by their supervisors using two validated researcher-made instruments. The data obtained were analyzed and interpreted using the mean, the Kruskal-Wallis test, the Mann-Whitney U test, and Spearman’s rho. The findings revealed that, taken as a whole, the practicum trainees of the University of Antique have excellent social skills. Regardless of their academic performance, students have the same excellent social-based skills level. They have different levels of social-based skills, though when classified according to their course. The trainees from the BSELT, BSIT, and BSHRM programs have excellent social-based skills, while the trainees from BSIE, BSAT, and BSET have very satisfactory social-based skills. As for family income, students from families with low, average, and high monthly income have excellent social-based skills. As to holders and non-holders of National Certificates, the study found that holders have excellent social-based skills. In contrast, non-holders have very satisfactory social-based skills. The study concluded that the practicum trainees of the University of Antique have outstanding performance in social-based skills. They have very good interpersonal and communication skills and need to deal with the people they come into contact with in their work. The University’s practicum trainees are spot-on. They possess the competencies required to perform the job to the fullest.